USING MULTI-CRITERIA DECISION MAKING METHODOLOGIES FOR STRATEGIC SUPPLY CHAIN DESIGN CHOICES; SELECTION OF THE BEST TRANSPORTATION SETUP AND DISTRIBUTION NETWORK EXPANSION PLAN - Al-Dali, Ibrahim H. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
Supply chain is considered as one of the key areas of companies’ success and it should be designed appropriately to be compatible with companies’ objectives and strategies. In this thesis, a case study of supply chain network redesign in oil and gas industry will be thoroughly studied, analyzed and concluded. This research has been applied and deployed on an oil and gas local company called “X-LUBE”. In brief, Multi-Criteria Decision Making (MCDM) approach is used to come up with the best transportation setup for X-LUBE distribution network among five available alternatives which are compared using predefined criteria. Several MCDM techniques were used such as AHP, TOPSIS, PROMETHEE and ELCTRE. Similarly; AHP technique were used to determine the expansion plan and strategies of X-LUBE distribution network along with associated cost and fleet type selection